L’ergonomie phénoménologique, champ de définition et lieu d’actualisation d’une écologie humaine - Éric Hamraoui (Activités)
The present contribution attempts to assess the importance for work thought of the dialogue established by Pierre Cazamian (1915-2012) between ergonomics and phenomenology. The meeting of these two disciplinary fields is part of the perspective of the foundation of a global ergonomics based on a systemic and multidisciplinary approach, inseparable from an analysis of the ’operativity’ of the strategies implemented by workers to counter the effects of alienated work in the Taylorian production system. It is an opportunity to take into account the role played by the resistance of reality in the manifestation of creativity at work, by the world of life in the constitution of science, and finally, by the body in the constitution of realities of being and dynamics of existence engaging the determinations of human praxis. These theoretical openings were made possible by reference to the phenomenologies of effort (Maine de Biran), of the body (Michel Henry), of consciousness (Husserl), of perception (Merleau-Ponty) and of the imagination (Gaston Bachelard). They also contribute to putting forward the founding idea of human ecology, considering work to be a living environment, a place of culture and a crossroads of planes of lived temporality. Finally, they allow us to conclude that the ergonomic approach has a contradictory dimension, that it is necessary to redefine the means available to reduce the constraints and annoyances weighing on the activity; to understand work as a ’psychic work’; and finally, to highlight the strength of the link between spatiality and activity.